Maximal Oxygen Uptake Is Achieved in Hypoxia but Not Normoxia during an Exhaustive Severe Intensity Run - Black, Matthew I.; Potter, Christopher R.; Corbett, Jo; Clark, Cain C. T.; Draper, Stephen B. (Frontiers in Physiology, 2017)
Highly aerobically trained individuals are unable to achieve maximal oxygen uptake (V˙O2max) during exhaustive running lasting ~2 min, instead V˙O2 plateaus below V˙O2max after ~1 min. Hypoxia offers the opportunity to study the (V˙O2) response to an exhaustive run relative to a hypoxia induced reduction in V˙O2max. The aim of this study was to explore whether there is a difference in the percentage of V˙O2max achieved (during a 2 min exhaustive run) in normoxia and hypoxia. Fourteen competitive middle distance runners (normoxic V˙O2max 67.0 ± 5.2 ml.kg−1.min−1) completed exhaustive treadmill ramp tests and constant work rate (CWR) tests in normoxia and hypoxia (FiO2 0.13). The V˙O2 data from the CWR tests were modeled using a single exponential function. End exercise normoxic CWR V˙O2 was less than normoxic V˙O2max (86 ± 6% ramp, P < 0.001). During the hypoxic CWR test, hypoxic V˙O2max was achieved (102 ± 8% ramp, P = 0.490). The phase II time constant was greater in hypoxia (12.7 ± 2.8 s) relative to normoxia (10.4 ± 2.6 s) (P = 0.029). The results demonstrate that highly aerobically trained individuals cannot achieve V˙O2max during exhaustive severe intensity treadmill running in normoxia, but can achieve the lower V˙O2max in hypoxia despite a slightly slower V˙O2 response.